Analgesia pós-operatória da dipirona em cadelas submetidas à ovario-histerectomia convencional ou videoassistida - Pohl, Virgínia Heinze (2014)
This thesis is subdivided in two scientific articles. The first one reports the use of dipyrone (25 mg/kg, TID) and N-butilescopolamine (0,2 mg/kg, TID) for postoperative analgesia following ovaryhisterectomy (OVH) in two bitches: one patient was submitted to conventional OVH and the other one to laparoscopic-assisted OVH. Postoperative pain was assessed using the University of Melbourne pain scale, starting at the first hour and up to 48 hours after the surgery. The animal submitted to conventional OVH required rescue analgesia. The analgesic protocol was effective in post-operative analgesia following laparoscopic-assisted OVH. Those results motivated continuing further investigation on such subject. The purpose of the second study was to evaluate the post-operative analgesia of dipyrone (25 mg/kg, QID) in eight bitches submitted to conventional OVH (GC) and eight bitches submitted to laparoscopic-assisted OVH (GV). Postoperative pain was evaluated using the visual analog scale (VAS), the University of Melbourne pain scale and the Glasgow short form pain scale, starting in the first hour up to 48 hours following surgery. Dipyrone was effective in both groups; no animal required rescue analgesia. Although there was not statistical difference between groups in most of the moments, animals in GV returned faster to baseline parameters. GV score was lower (p < 0.01) in the first postoperative hour using the Melbourne scale and at 24 hours using the VAS scale. In conclusion, 25 mg/kg of dipyrone given q.i.d. provides effective postoperative analgesia in bitches submitted to conventional and laparoscopic-assisted OVH, if the surgical technique presented in this study is strictly used. Moreover, laparoscopic-assisted OVH provided less postoperative pain.